Molecular dynamics investigation of membrane fouling in organic solvents - Ma, Yunqiao (2022)
Membrane fouling, which is a key obstacle in implementing membrane technology, has been studied extensively for aqueous feeds. With increasing interests in organic solvent applications, a corresponding effort on understanding membrane fouling is warranted. This study employs molecular dynamics simulations to unveil the mechanisms underlying the different adsorption behaviors of dextran onto a polyacrylonitrile (PAN) membrane in three polar and protic solvents, namely, water, formamide and ethanol. The dextran-membrane separation distance is the lowest for water, followed by ethanol then formamide, which agrees with the worse flux decline for water relative to formamide observed experimentally. The greatest adsorption tendency in water is tied to the most attractive dextran-membrane interaction. On the other hand, the lower adsorption tendency in formamide and ethanol is linked to enhanced solvation of the dextran molecule and membrane, which deters dextran adsorption onto the membrane. Specifically, formamide, which leads to the least adsorption, exhibits the most attractive solvent-dextran and solvent-membrane interaction energies, the highest solvent-accessible surface area (SASA) for dextran, and also the highest density of solvent molecules in the solvation shell closest to the membrane. As for ethanol, it gives the highest density of solvent molecules in the solvation shell closest to a part of the dextran. The solvation of foulant and membrane by water deviates from that by other similarly polar and protic solvents, which has important implications in membrane fouling and highlights the need for enhancing the understanding of membrane fouling behaviors in organic solvents.